2005
DOI: 10.1111/j.1365-2842.2005.01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface EMG of jaw elevator muscles: effect of electrode location and inter‐electrode distance

Abstract: SUMMARY This study addresses methodological issues on surface electromyographic (EMG) signal recording from jaw elevator muscles. The aims were (i) to investigate the sensitivity to electrode displacements of amplitude and spectral surface EMG variables, (ii) to analyse if this sensitivity is affected by the inter-electrode distance of the bipolar recording, and (iii) to investigate the effect of interelectrode distance on the estimated amplitude and spectral EMG variables. The superficial masseter and anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 28 publications
3
111
0
4
Order By: Relevance
“…This procedure is carried out with electrodes placed on patients' skin, in general bilaterally. Its relatively technical simplicity allows its use in Dentistry and in clinical research 4 . TMDs investigation and evaluation should include behavioral, emotional and psycho-social factors, in addition to normally observed physical changes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This procedure is carried out with electrodes placed on patients' skin, in general bilaterally. Its relatively technical simplicity allows its use in Dentistry and in clinical research 4 . TMDs investigation and evaluation should include behavioral, emotional and psycho-social factors, in addition to normally observed physical changes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that surface EMG recordings were influenced by location of the electrodes over the muscle, inter-electrode distance, body posture and psychological factors [25][26][27]. The electrode location has a large influence especially on characteristics of the recorded EMG signal.…”
Section: Effect Of Location In the Surface Emg Recordingmentioning
confidence: 99%
“…The subjects were comfortably installed in a chair inside a room with a controlled temperature (22 °C) for 30 minutes. Bipolar surface electrodes (Kendall MedTrace 100 Conductive Adhesive ECG Electrodes, Tyco Healthcare Group LP, Pointe-Claire, Canada) were placed with a distance of 18 mm between them, following the long axis of the muscle fibers of the masseter and anterior temporal muscle on both sides 4,5 ( Figure 1). These electrodes were linked by wires to an amplifier connected to a computer for recording and analysis of muscle activity splint and 4 th and 5 th records were obtained following the same criteria used for the 2 nd and 3 rd records.…”
Section: Electromyographic Evaluation (Emg)mentioning
confidence: 99%
“…distance between the electrodes and the thickness of the fat layer between the skin and muscles. 4,5 The muscle parameters frequently studied by EMG include postural position or rest, as well as activity during maximum tooth clenching. Such parameters have been used to evaluate the effect of occlusion on normal muscle function, both with and without an interocclusal splint.…”
Section: Introductionmentioning
confidence: 99%